2024
DOI: 10.1126/sciadv.adi5501
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-based inhibition of vascular endothelial growth factor receptors alleviates osteoarthritis pain and cartilage damage

Kaige Ma,
Tiep Pham,
Jun Wang
et al.

Abstract: Osteoarthritis (OA) is characterized by cartilage damage, inflammation, and pain. Vascular endothelial growth factor receptors (VEGFRs) have been associated with OA severity, suggesting that inhibitors targeting these receptors alleviate pain (via VEGFR1) or cartilage degeneration (via VEGFR2). We have developed a nanoparticle-based formulation of pazopanib (Votrient), an FDA-approved anticancer drug that targets both VEGFR1 and VEGFR2 (Nano-PAZII). We demonstrate that a single intraarticular injection of Nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Innovative studies from animal models reported on the use of microgels and hydrogels with a microencapsulation of stem cells in order to protect the injected cells, prolonging in vivo retention and widening the therapeutic window [124]. Jonhbosco et al demonstrated that the injection of microencapsulated MSC in OA rat joints showed a significant reduction in cartilage degradation and matrix loss [125]. Furthermore, even more recently, Ma et al developed a nanoparticle-based formulation of pazopanib, an FDA-approved anticancer drug that targets both VEGFR1 and VEGFR2.…”
Section: Innovation In Osteoarthritis Therapymentioning
confidence: 99%
“…Innovative studies from animal models reported on the use of microgels and hydrogels with a microencapsulation of stem cells in order to protect the injected cells, prolonging in vivo retention and widening the therapeutic window [124]. Jonhbosco et al demonstrated that the injection of microencapsulated MSC in OA rat joints showed a significant reduction in cartilage degradation and matrix loss [125]. Furthermore, even more recently, Ma et al developed a nanoparticle-based formulation of pazopanib, an FDA-approved anticancer drug that targets both VEGFR1 and VEGFR2.…”
Section: Innovation In Osteoarthritis Therapymentioning
confidence: 99%